Ancestors, Embodiment and Sexual Desire: Wild Religion and the Body in the Story of a South African Lesbian Sangoma - Van Klinken, A. S. (Body and religion, 2017)
This article explores the intersections of religion, embodiment, and queer sexuality in the autobiographical account of a South African self-identifying lesbian sangoma', on the basis of the book Black Bull, Ancestors and Me: My Life as a Lesbian Sangoma, by Nkunzi Zandile Nkabinde. The article offers an intertextual reading of this primary text, first vis-à-vis David Chidester's Wild Religion: Tracking the Sacred in South Africa, and second, vis-à-vis some black lesbian feminist writings, specifically by Audre Lorde, M. Jacqui Alexander, and Gloria Wekker. This intertextual reading foregrounds the embodied and in fact queer nature of the wild forces of indigenous religion in contemporary South Africa, and it illuminates how embodied and erotic experience is grounded in the domain of the sacred. Hence, the article concludes by arguing for a decolonising and post-secular move in the field of African queer studies, underlining the need to take the sacred seriously as a site of queer subjectivity.